Unequal Cities : Structural Racism and the Death Gap in America's Largest Cities - De Maio, Fernando, 1976-; Benjamins, Maureen R. (Health equity in America., 2021)
"The contributors to this edited volume explore the degree to which racial health disparities affect death rates in America's 30 largest cities. By examining mortality statistics related to leading causes of death, they are able to show that each of the cities in question has some serious work to do and that in many places the differences are more or less pronounced than in others"--